Scoping carbon dioxide removal options for Germany–What is their potential contribution to Net-Zero CO2? - Borchers, Malgorzata; Thrän, Daniela; Chi, Yaxuan; Dahmen, Nicolaus; Dittmeyer, Roland; Dolch, Tobias; Dold, Christian; Förster, Johannes; Herbst, Michael; Heß, Dominik; Kalhori, Aram; Koop-Jakobsen, Ketil; et al. (Frontiers in Climate, 2022)
The Paris climate agreement outlines that, to meet its temperature goal, we need to balance anthropogenic greenhouse gas emissions with sinks. Carbon Dioxide Removal (CDR) is considered a key element to reaching that goal. There are currently a wide variety of CDR measures available. Their implementation, and accordingly their potential, however, depends on site specific conditions, such as biophysical conditions, availability of infrastructure, social acceptance, regulatory frameworks and policy instruments in place. In our study we investigated various near-to-market CDR options for Germany, which we present in the form of thirteen dedicated model concepts. They cover technical CO2 removal (two models of direct air carbon capture, i.e. DACC), hybrid solutions (six bioenergy with carbon capture technologies, i.e., BECC) and five options for natural sink enhancement, so-called Nature-Based Solutions (NBS). Our estimates for their CO2 removal potentials in 2050 range from 0.4 to 30 million tonnes CO2, depending on the option. Ten of thirteen model concepts provide technical removal potentials higher than 1 million tonnes CO2 per year. To complement the necessary information on technology-based and hybrid options we also provide an overview on possible solutions for CO2 storage for Germany. Taking biophysical conditions and infrastructure into account, northern Germany seems a preferable area for deployment of many concepts. However, for their successful implementation further socio-economic analysis, clear regulations, and policy incentives are necessary.